2023
DOI: 10.3389/fpls.2022.1092610
|View full text |Cite
|
Sign up to set email alerts
|

Integrated diagnosis and time-series sensitivity evaluation of nutrient deficiencies in medicinal plant (Ligusticum chuanxiong Hort.) based on UAV multispectral sensors

Abstract: BackgroundNitrogen(N), phosphorus(P), and potassium(K) are essential elements that are highly deficient during plant growth. Existing diagnostic methods are not suitable for rapid diagnosis of large-scale planting areas. Near-ground remote sensing technology based on unmanned aerial vehicle (UAV) and sensor is often applied to crop growth condition monitoring and agricultural management. It has been proven to be used for monitoring plant N, P, and K content. However, its integrated diagnostic model has been le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The current study found that the value of FI was greater than 1.9 under all treatments, suggesting that microbial metabolism provides the majority of DOM [ 56 ]. Moreover, the value of the BIX lower than 1 under all treatments indicated the autochthonous or biological production of DOM components sourced from terrestrial DOM [ 57 ]. In addition, the FI decreased with the biochar and straw treatment ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study found that the value of FI was greater than 1.9 under all treatments, suggesting that microbial metabolism provides the majority of DOM [ 56 ]. Moreover, the value of the BIX lower than 1 under all treatments indicated the autochthonous or biological production of DOM components sourced from terrestrial DOM [ 57 ]. In addition, the FI decreased with the biochar and straw treatment ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing image characteristics facilitated the monitoring, diagnosis, and comprehension of plant growth status, enabling the accurate regulation and management of plant growth [1]. Several studies showed that crop quantitative remote sensing was effective in reflecting actual nitrogen levels and monitoring nitrogen across various cereal crops [2][3][4]. Mullan [5] used a digital image analysis tool for high-throughput screening of four large wheat populations to validate the relationship between digital image analysis and measures of the normalized difference vegetation index (NDVI), leaf area index, and light penetration through the crop canopy.…”
Section: Introductionmentioning
confidence: 99%